Coastal erosion, global sea‐level rise, and the loss of sand dune plant habitats. Issue 7 (1st September 2005) - Feagin, Rusty A.; Sherman, Douglas J.; Grant, William E.
Abstract : Much of America's coastline is threatened by overdevelopment and coastal erosion, driven by global sea‐level rise, a problem that is attracting the attention of researchers around the world. Although we have now acknowledged the impending risks, little is known about the response of spatially dependent dune plant communities to the loss or restriction of their habitat. In order to study this development, a spatially explicit model of sand dune plant succession on Galveston Island, Texas, was created, using sea‐level rise as the primary mechanism causing local erosion. Simulations of sea‐level rise scenarios developed by the Intergovernmental Panel on Climate Change demonstrated that beach erosion constrained plants to a narrow area, resulting in a breakdown of the successional process. The loss of late‐succession plants along coastlines, their dependent faunal species, and possible solutions are discussed. This model and example serves as a harbinger of the future for many of the US's sandy beaches and coastal communities.